Peningkatan Kemampuan Menstrual Hygiene Melalui Pendekatan Health Literacy pada Remaja Putri Menarche - Dina Zakiyyatul Fuadah; Andika Siswoaribowo; Agnes Eka Alfionita (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
The menstrual hygiene behavior of adolescents, especially those in the menarche phase, still needs more attention. This study aims to evaluate menstrual hygiene practices among adolescent girls experiencing menarche at SMPN 4 Pare in Kediri. The study used a correlational research design with a cross-sectional approach. The population consisted of 40 female students, and a total sampling technique was used to select 40 respondents. The independent variable is health literacy and the dependent variable is menstrual hygiene ability. The E-Health questionnaire was used to assess health literacy, and the Menstrual Hygiene questionnaire was used to assess menstrual hygiene skills. Spearman rank statistical tests were used, and the results showed that 72.5% had poor health literacy and 67.5% had poor menstrual hygiene skills. The p-value was 0.001, which is less than the alpha level of 0.05 (r = 0.879). Health literacy greatly affects adolescents' ability to implement menstrual hygiene. Efforts are needed to increase interest in health literacy, especially among adolescents in the field of reproductive health.